2017
DOI: 10.3389/fphys.2017.00082
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Evaluation of Respiratory Pathophysiology during Exercise in Chronic Lung Diseases

Abstract: Dyspnea and exercise limitation are among the most common symptoms experienced by patients with various chronic lung diseases and are linked to poor quality of life. Our understanding of the source and nature of perceived respiratory discomfort and exercise intolerance in chronic lung diseases has increased substantially in recent years. These new mechanistic insights are the primary focus of the current review. Cardiopulmonary exercise testing (CPET) provides a unique opportunity to objectively evaluate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 264 publications
(433 reference statements)
2
63
1
4
Order By: Relevance
“…Peak-VO 2 Kg is the gold standard for the evaluation of cardiopulmonary fitness, Max-VO 2 Kg is used to evaluate endurance, and AT-VO 2 Kg is used in the evaluation of aerobic exercise capacity. 21 The present study showed that exercise endurance evaluation indexes such as AT-VO 2 Kg, Max-VO 2 Kg, AT-O 2 puls, AT-Load, AT-Mets, and Max-Mets were improved after EECP therapy in the general population without cardiovascular diseases. This suggests that EECP can generally improve exercise endurance.…”
Section: Discussionsupporting
confidence: 51%
“…Peak-VO 2 Kg is the gold standard for the evaluation of cardiopulmonary fitness, Max-VO 2 Kg is used to evaluate endurance, and AT-VO 2 Kg is used in the evaluation of aerobic exercise capacity. 21 The present study showed that exercise endurance evaluation indexes such as AT-VO 2 Kg, Max-VO 2 Kg, AT-O 2 puls, AT-Load, AT-Mets, and Max-Mets were improved after EECP therapy in the general population without cardiovascular diseases. This suggests that EECP can generally improve exercise endurance.…”
Section: Discussionsupporting
confidence: 51%
“…A high level of V D EELV "buoyed" the expandable basic lung volume above its position, meaning that V T had limited room to expand downwards so that it could not help but invade upwards to the OT or near its limit (Figure 2). In COPD, decreased OT [3,22] and increased DH have been reported to be possible causes of exercise limitation [30], although some studies have questioned whether DH occurs in all COPD patients [31][32][33]. These previous studies have measured DH peak but not included V Dpeak .…”
Section: The % Of Tlcmentioning
confidence: 99%
“…Since DH may not occur in all COPD patients [31][32][33], as VDDHpeak% and VDEELVpeak% are substantially 310 larger and slightly more related to dyspnea [31] and exercise capacity than DH% and EELV%, and as VTpeak% 311…”
Section: Clinical Implications Of Vddhpeak% and Vdeelvpeak% And Vtpementioning
confidence: 99%
See 1 more Smart Citation
“…Patients require significant less ventilation to perform the same level of exercise after exercise training. In turn, this reduction in the minute ventilation prevent, or at least improves, the potential development of dynamic hyperinflation 80 . Moreover, the reduction of lactate production results in improvement in muscle fatigue 77,78 .…”
Section: Aerobic and Combined (Aerobic And Resistance) Trainingmentioning
confidence: 99%